Respuesta :
[tex]\bf \begin{cases} f(x)=4x-1\\ g(x)=x^2+7 \end{cases}~\hspace{7em}g(~~~f(x)~~~)=[~f(x)~]^2+7 \\\\\\ g(~~~f(x)~~~)=[~4x-1~]^2+7\implies g(~~~f(x)~~~)=(4x-1)(4x-1)+7 \\\\\\ g(~~~f(x)~~~)=\stackrel{\mathbb{F ~O~ I~ L}}{(16x^2-8x+1)}+7\implies g(~~~f(x)~~~)=16x^2-8x+8[/tex]
Answer
[tex]g(f(x)) = = 16 {x}^{2} - 8x + 8[/tex]
step by step Explanation
The functions given are
[tex]f (x)= 4x- 1[/tex]
[tex]g(x)= {x}^{2} + 7[/tex]
We want to find:
[tex]g(f (x))= g( 4x- 1)[/tex]
This implies that
[tex]g(f (x))= ( (4x- 1)^{2} + 7) [/tex]
Let us now simplify
[tex]( {a - b)}^{2} = {a}^{2} -2ab + {b}^{2} [/tex]
This implies that
[tex] ( (4x- 1)^{2} + 7) =( {(4x)}^{2} - 2(4x) \times 1 + 1 [/tex]
Combine the terms to get,
[tex] = 16 {x}^{2} - 8x + 1 + 7[/tex]
[tex] = 16 {x}^{2} - 8x + 8[/tex]
[tex]g(f(x)) = = 16 {x}^{2} - 8x + 8[/tex]
step by step Explanation
The functions given are
[tex]f (x)= 4x- 1[/tex]
[tex]g(x)= {x}^{2} + 7[/tex]
We want to find:
[tex]g(f (x))= g( 4x- 1)[/tex]
This implies that
[tex]g(f (x))= ( (4x- 1)^{2} + 7) [/tex]
Let us now simplify
[tex]( {a - b)}^{2} = {a}^{2} -2ab + {b}^{2} [/tex]
This implies that
[tex] ( (4x- 1)^{2} + 7) =( {(4x)}^{2} - 2(4x) \times 1 + 1 [/tex]
Combine the terms to get,
[tex] = 16 {x}^{2} - 8x + 1 + 7[/tex]
[tex] = 16 {x}^{2} - 8x + 8[/tex]